Consumer knowledge, attitude, and perception toward microalgae as food in the Philippines - Acosta, Leila Sigrid A. (College of Home Economics, University of the PHilippines Diliman, 2024)
While microalgae are considered to be great alternative food due to their nutritional composition and imparted benefits, there is an evident lack of available microalgae-containing products in the market. To better understand their application as food in the Philippines, the study determined the Filipino consumers’ knowledge, attitude, and perception (KAP) towards the use of microalgae as food in the Philippines. A survey questionnaire was administered among 400 Filipino respondents composed of both male and female, aged 18-59 yrs old. Results showed that respondents had average knowledge about microalgae with mean scores being significantly different (p<0.05) among various age groups, educational attainment, and household income. Majority of respondents strongly agreed that microalgae is innovative and interesting but the lack of available information about it deters consumers to be informed further. Factor analysis revealed that attitudes toward microalgae are influenced by perceived benefits, expected sensory quality of food, and food product information. Overall, the study showed that microalgae is positively perceived by Filipino consumers despite the lack of information available to the general public and that there is interest in these innovative products. Findings from this study could be used by government agencies and food manufacturing companies as a basis for the need of proper risk assessment and risk communication to inform consumers about the benefits of microalgae as food.